2014
DOI: 10.1371/journal.pone.0096322
|View full text |Cite
|
Sign up to set email alerts
|

Acculturative Stress and Influential Factors among International Students in China: A Structural Dynamic Perspective

Abstract: Stress represents a prominent aspect of modern life and is associated with numerous negative health consequences. International students are a key force in shaping globalization. However, these students often experience acculturative stress, influencing their health and well-being. The growing number of international students in China emerges as a new global health challenge and presents an opportunity to advance our understanding of acculturative stress. This study aims to investigate the acculturative stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 26 publications
3
54
0
Order By: Relevance
“…A novel contribution of our study is the verification of the inter-relationship among the seven acculturative stress components (Yu et al, 2014a) and depression. The path analysis demonstrated the key role of selfconfidence in predicting CES-D 10 scores.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A novel contribution of our study is the verification of the inter-relationship among the seven acculturative stress components (Yu et al, 2014a) and depression. The path analysis demonstrated the key role of selfconfidence in predicting CES-D 10 scores.…”
Section: Discussionmentioning
confidence: 91%
“…International students in China are a growing and at‐risk population for acculturative stress and depression. With data from the International Student Health and Behaviour Survey (Yu et al, ) in China, seven acculturative stress components were detected in a previous study (Yu et al, ), including a central component (self‐confidence), three distal components (value conflict, identity threat and rejection) and three proximal components (poor cultural competence, opportunity deprivation and homesickness). The current study extended the previous study to investigate the relationship between these components and depression with data also from International Student Health and Behaviour Survey.…”
mentioning
confidence: 97%
“…More specifically, the common challenges that international students encounter include language barriers, perceived discrimination, financial concerns, homesickness, academic pressure and culture shock [12] [13] [14]. Similarly, several studies conducted among international students studying in China revealed that the students experienced mental health problems, such as stress and depression as a result of acculturative stressors [15] [16] [17]. In light of the psychological adjustment difficulties and their devastating impact on psychological well-being, numerous researchers have at- [9] [10] [25].…”
Section: Introductionmentioning
confidence: 99%
“…Because of mixed and debatable findings, there is no definite conclusion about the nature of the association between acculturative stress and marital status. According to Ahalya and Berry [31], unmarried individuals experienced greater acculturative stress than married ones, and the finding contradicted the finding of Yu, Chen [32].…”
Section: Acculturative Stress and Sociodemographicsmentioning
confidence: 91%
“…Educational level. In some studies, acculturative stress has also been found associated with the educational qualification of participants, indicating that bachelor students experience less acculturative stress than master and doctorate students [32].…”
Section: Acculturative Stress and Sociodemographicsmentioning
confidence: 99%